Novel role of circRNAs in the drug resistance of gastric cancer: regulatory mechanisms and future for cancer therapy - Lu, Ling; Gao, Zihan; Jin, Longtao; Geng, Hao; Liang, Zhaofeng (Frontiers in Pharmacology, 2024)
Cancer, including gastric cancer, has become a serious disease that jeopardizes public life. Currently, the main treatment methods are surgery, radiation therapy, and chemotherapy. One of the primary causes of death for patients with gastric cancer is drug resistance. Several mechanisms of anticancer drugs resistance have been reported, including changes in drugs transport and metabolism, mutations in drug targets, changes in DNA repair systems, inhibition of cell apoptosis and autophagy, gastric cancer stem cells, invasion and migration. It is becoming more widely known that noncoding RNAs, like circRNAs, play a critical role in the resistance of drugs used to treat gastric cancer. CircRNAs have a unique structure and function that is related to gastric cancer resistance, cell proliferation, apoptosis, autophagy, DNA repair systems, migration, and invasion. A clear understanding of the molecular mechanism of circRNAs mediated the resistance of gastric cancer drugs will open a new window for the treatment and management of gastric cancer. Therefore, in this review, we will summarize the current mechanism of drug resistance, and finally discuss the molecular mechanism of circRNAs in regulating the development of drug resistance in gastric cancer.